2010
DOI: 10.3126/ajms.v1i1.2927
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Nutritional Status of the Under Five Children

Abstract: Objective: To identify factors associated to the nutritional status of under five children. Method:The data used in this analysis are from Demographic and Health Survey 2006 conducted in Nepal. Total 5262 cases are included in the present study. A multinomial logistic regression model is used to study the relation between various factors and nutritional status. Results:Increasing body mass index of mothers and wealth index shows decreasing likelihood of malnutrition among children. Rural children show insignif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 2 publications
6
12
0
Order By: Relevance
“…The higher percentage of stunting in this study could be because of the fact that this study was conducted within the hilly region. Similar findings have been reported in various studies (Nepal Ministry of Health and Population, New ERA and ICF International, 2012;DoHS, 2016;Pradhan, 2010).…”
Section: Discussionsupporting
confidence: 78%
“…The higher percentage of stunting in this study could be because of the fact that this study was conducted within the hilly region. Similar findings have been reported in various studies (Nepal Ministry of Health and Population, New ERA and ICF International, 2012;DoHS, 2016;Pradhan, 2010).…”
Section: Discussionsupporting
confidence: 78%
“…[14][15][16][17] In this study the prevalence of wasting was found to be higher among children living in urban areas similar to a study done by Kavosi et al 13 Other studies however showed that prevalence of wasting is higher in rural areas. 15,17,18 In the present study there was no much difference between children attending rural and urban Anganwadi centres with respect to mid arm circumference measuring less than 13.5cms. However in a study conducted by Mishra and Mishra proportion of children with mid arm circumference measuring less than 13.5cms was found to be higher in rural compared to urban areas.…”
Section: Discussionsupporting
confidence: 73%
“…[14][15][16] Prevalence of stunting in our study was higher among children living in urban areas which was similar to a study done by Kavosi et al 13 In contrary other studies showed that the prevalence of stunting is higher in rural areas. [14][15][16][17] In this study the prevalence of wasting was found to be higher among children living in urban areas similar to a study done by Kavosi et al 13 Other studies however showed that prevalence of wasting is higher in rural areas. 15,17,18 In the present study there was no much difference between children attending rural and urban Anganwadi centres with respect to mid arm circumference measuring less than 13.5cms.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Malnutrition is a major public health and nutrition problem in Nepal. It is a major underlying cause of the child morbidity and mortality in Nepal [1][2][3]. Nutrition is the sum of total process involved in utilization of food substance with growth, repair and maintenance of body accomplished.…”
Section: Introductionmentioning
confidence: 99%